2019
DOI: 10.1016/j.snb.2019.02.042
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal quantum dot-based surface acoustic wave sensors for NO2-sensing behavior

Abstract: Highlights the trapping of NO2 molecules in the porous structure and thus making the film stiffer. Moreover, the Pb(NO3)2-treated sensor showed good stability and selectivity at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 52 publications
1
38
0
Order By: Relevance
“…The frequency shis of SAW sensor is mainly dependent on the following three factors: mass load, elastic changes in elasticity and acousto-electric interaction. 21,22 The equation representing the contributions of these three factors is:…”
Section: Resultsmentioning
confidence: 99%
“…The frequency shis of SAW sensor is mainly dependent on the following three factors: mass load, elastic changes in elasticity and acousto-electric interaction. 21,22 The equation representing the contributions of these three factors is:…”
Section: Resultsmentioning
confidence: 99%
“…Also, it can be observed that the heat treatment applied to the films considerably improves their properties, especially for the films with QDs. This heat treatment has the role of removing organic residues present in the film from the solvents used and promoting the penetration of gas molecules in the volume of the film, due to the formation of cracks on their surface [11].…”
Section: Resultsmentioning
confidence: 99%
“…QDs are crystalline nanoparticles with small sizes (1–12 nm) [10]. Considering this aspect, the use of QDs for the synthesis of sensitive films represents a relatively new and interesting direction of research [11,12]. One of the synthesis methods for QDs, which ensures the control of the morphology and high purity, is pulsed laser deposition (PLD) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The LOD of the Ag/PPy L-SAW sensors (defined as the concentration providing a signal-to-noise ratio of at least three [23]) was estimated to be 3, 5 and 20 ppb for acetone, ethanol and toluene, respectively. These LOD are below the limits set for acetone, ethanol and toluene in different areas.…”
Section: Gas Sensing Properties Of the L-saw Sensorsmentioning
confidence: 99%